Analisis uji efektivitas LKS virtual laboratory pada materi fluida dinamis dan suhu kalor kelas XI SMAN 15 Padang - Nur Sahfitri; Yenni Darvina; Masril Masril; Hidayati Hidayati (Universitas Negeri Padang, 2019)
Physics learning in schools requires students to carry out practical work in achieving skills competencies. To fulfill practical activities, complete laboratory equipment and Student Worksheets (LKS) are needed. However, practicum tools and Student Worksheets at SMAN 15 Padang schools are still incomplete and inadequate. Therefore, the assisted virtual practicum of the virtual laboratory Student Worksheet is a solution to replace the real lab. The purpose of this study was to examine the effectiveness of virtual laboratory LKS in dynamic fluid material and heat temperature of class XI of SMAN 15 Padang. To examine the effectiveness of the virtual laboratory Student Worksheet, a Pre-Experimental Design study was conducted with one-group pretest-posttest design research design. This research was conducted in class XI MIA 1 of SMAN 15 Padang by applying the virtual laboratory Student Worksheet and looking at the effectiveness of the virtual laboratory Student Worksheet in achieving student attitudes, knowledge and skills competencies. Students' attitude competencies are assessed during seven meetings. The competency of student knowledge was analyzed by comparing the value of the pretest and posttest of students using the N-gain test and the correlated t test. Skills competencies are valued at each virtual lab. Based on the research that has been done, spiritual attitude competence, discipline, self-confidence, honesty and student cooperation always increase every meeting, this means that the Student Laboratory Worksheet can change students' attitudes to be better in each learning process. In knowledge competency, there was a significant difference in the pretest and posttest as evidenced by the N-gain value of 0.72 with high criteria, meaning that the difference in values was very significant. In addition, the correlated t test proves that the hypothesis of the effectiveness of the virtual laboratory Student Worksheet is accepted with a value of -13.96 smaller than ttable at the error rate of 5% and the degree of freedom 30 with a value of 1.697. The results of skills competency research prove that student grades increase every time the experiment is conducted, because students are increasingly proficient in conducting experiments with the help of the virtual laboratory Student Worksheet. Therefore, it is concluded that the virtual laboratory Student Work Sheet is effective for use in dynamic fluid material and heat temperature of class XI of SMAN 15 Padang.